Emergent Magnetic Phenomenon with Unconventional Structure in Epitaxial Manganate Thin Films. Issue 13 (6th May 2021) - Yang, Mingwei; Jin, Kuijuan; Yao, Hongbao; Zhang, Qinghua; Ji, Yiru; Gu, Lin; Ren, Wenning; Zhao, Jiali; Wang, Jiaou; Guo, Er‐Jia; Ge, Chen; Wang, Can; et al.
Abstract: A variety of emergent phenomena are enabled by interface engineering in the complex oxides heterostructures. While extensive attention is attracted to LaMnO3 (LMO) thin films for observing the control of functionalities at its interface with substrate, the nature of the magnetic phases in the thin film is, however, controversial. Here, it is reported that the ferromagnetism in two and five unit cells thick LMO films epitaxially deposited on (001)‐SrTiO3 substrates, a ferromagnetic/ferromagnetic coupling in eight and ten unit cells ones, and a striking ferromagnetic/antiferromagnetic pinning effect with apparent positive exchange bias in 15 and 20 unit cells ones are observed. This novel phenomenon in both 15 and 20 unit cells films indicates a coexistence of three magnetic orderings in a single LMO film. The high‐resolution scanning transmission electron microscopy suggests a P21 /n to Pbnm symmetry transition from interface to surface, with the spatial stratification of MnO6 octahedral morphology, corresponding to different magnetic orderings. These results can shed some new lights on manipulating the functionality of oxides by interface engineering. Abstract : Unconventional P21 /n structure has only been predicted theoretically in LaMnO3 films previously. This work demonstrates the experimental observation of the emergent magnetic orders including ferromagnetism and antiferromagnetism, strongly correlated with the octahedral distortion in P21 /n and Pbnm structures in different layers of LaMnO3 ultrathin films, respectively, which opens a window for engineering functionality via interfacial symmetry breaking.